Military staff study as a tool for language policy design: A case of establishing the RTN’s English tests - Jarayapun, Jitpicha (Journal of Interdisciplinary Studies in Education, 2024)
A staff study (SS) is an administrative tool used for decision making which involves data gathering and analysis to determine the proper resolution to an issue. SS is also used in the areas of the military which are mostly assigned with classified information; as a result, resources regarding staff studies are still restricted or available in limited amounts. Furthermore, SS is rational and applicable in interdisciplinary academic fields; especially, in an area of policy design. This article proposes the value of such a study in education policy making through its application in the specific investigation of English testing development in the Royal Thai Navy (RTN). It articulated that a SS shares similar purpose to applied research in language education; yet, it is more focused on applying knowledge to problem solutions and circumstances. Though SS does not prepare to build or extend knowledge and expertise, its principle enacts a logical model guiding all existing context variables into the study. Thus, it can provide a thinking springboard for solving problems in language education. Finally, it can create a possible innovative way to deal with unique problems while further experimental process with the data analysis can justify research in language education.